Effect of bioinoculants and fertility levels on growth, yield attributes and yield of safflower (Carthamus tinctorius) - BODKHE, A.A.; ISMAIL, SYED (Annals of Agricultural Research, 2016)
Field experiments were conducted during Rabi seasons of 2009 and 2010 at Department of Soil Science and Agricultural Chemistry, VN Marathwada Agricultural University, Parbhani to study the effect of biofertilizers and fertility levels on growth, yield attributes, yield and quality of safflower. The experimental soil was clay in texture with pH 8.3, moderate fertility, low in organic carbon and available nitrogen, medium in phosphorus and high in potassium. Treatments comprised of three fertility levels (100% RDF, 75% RDF and control) and four levels of bioinoculants (Azotobacter, PSB, Azotobacter + PSB and no inoculation). The experiment was laid out in a factorial randomized block design with four replications. The results revealed that application of RDF (20 kg N + 20 kg P2O5 ha-1) recorded significantly higher seed and straw yield due to significantly higher number of capsules, plant height and 100 seed weight. Dual inoculation of seeds with Azotobacter + PSB recorded significantly higher yield attributes, seed and straw yields over uninoculated control and alone application of bioinoculants.